1990
DOI: 10.1164/ajrccm/141.5_pt_1.1136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exposures to Ambient Ozone on Ventilatory Lung Function in Children

Abstract: This study was undertaken to determine if the ventilatory capacity of children is affected by hourly concentrations of ozone inhaled during their daily activity. Over a 3-wk period (June-July 1987) children who were attending a summer camp in the San Bernardino mountains of California performed spirometry up to three times per day during their stay at the camp. A total of 43 children were tested a total of 461 times. Ozone, oxides of nitrogen, sulfur dioxide, temperature, and relative humidity were measured co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 6 publications
1
33
0
2
Order By: Relevance
“…Atopy did not play a significant role in any associations except for exhaled NO levels. A reasonable conclusion is that even if smaller groups are evaluated in such translational exposure studies, real-world ozone levels did demonstrate biologically and scientifically plausible associations, underscoring other investigators' premise that controlled chamber studies likely underestimate the effects of true outdoor air pollutants (11,17). Ambient posted monitors have been used thus far to evaluate lung health and ozone levels (20,50).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Atopy did not play a significant role in any associations except for exhaled NO levels. A reasonable conclusion is that even if smaller groups are evaluated in such translational exposure studies, real-world ozone levels did demonstrate biologically and scientifically plausible associations, underscoring other investigators' premise that controlled chamber studies likely underestimate the effects of true outdoor air pollutants (11,17). Ambient posted monitors have been used thus far to evaluate lung health and ozone levels (20,50).…”
Section: Discussionmentioning
confidence: 92%
“…Large cohort studies have demonstrated worsening of lung function, i.e., decrement in morning peak flow rates or small airways function, in the days after elevated atmospheric ozone levels (8,10). Although asthmatics are particularly susceptible to the harmful effects of ozone air pollution, controlled exposure chamber studies demonstrated acutely diminished lung function in asthmatics as well as healthy individuals after being exposed to high concentrations of ozone (11)(12)(13). The capacity to induce pulmonary function alterations depends on ozone levels, duration and pattern of exposure, and respiratory minute volume (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…McDonnell and colleagues (5) This article presents the results of our reanalysis of the original lung function and 03 data from six recent summer camp studies. These studies indude two in northwestern New Jersey (3,11), two in southern California (6,9), and two in Ontario (8,12 The Lake Couchiching study was conducted collaboratively by Health and Welfare Canada and Harvard University over 10 days in late June and early July of 1983 (7,12). Lung function data were collected twice daily (0730-0930 hr and 1630-1830 hr) for 52 campers (including 23 asthmatics: 12 males and 11 females, and 29 nonasthmatics: 16 males and 13 females), who ranged from 7 to 15 years of age.…”
mentioning
confidence: 99%
“…The first took place at a church-sponsored summer camp in the San Bernardino Mountains (elevation 1740 m) (6 Working data sets for each study reviewed above were obtained either directly from members of the original study teams, or through third parties (see Acknowledgments). A common feature of all six data sets was the availability of afternoon spirometric lung function data collected over many days on many subjects, along with the previous 1-hr average 03 concentrations.…”
mentioning
confidence: 99%